2023
DOI: 10.3390/nu15234969
|View full text |Cite
|
Sign up to set email alerts
|

Myths and Facts about Food Intolerance: A Narrative Review

Fabiana Zingone,
Luisa Bertin,
Daria Maniero
et al.

Abstract: Most adverse reactions to food are patient self-reported and not based on validated tests but nevertheless lead to dietary restrictions, with patients believing that these restrictions will improve their symptoms and quality of life. We aimed to clarify the myths and reality of common food intolerances, giving clinicians a guide on diagnosing and treating these cases. We performed a narrative review of the latest evidence on the widespread food intolerances reported by our patients, giving indications on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 206 publications
0
2
0
Order By: Relevance
“…For this reason, although LM is a necessary precondition for LI, it is not sufficient since LM can have primary or secondary causes. In addition, there is no matching between symptomatology and a positive test for LI [ 109 ]. Lactase non-persistence (LNP) is the primary cause of LM, due to reduction in expression of lactase levels during the first two decades of life, while lactase persistence (LP) derives from specific mutations.…”
Section: Lactase Deficiency and Lactose Intolerancementioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, although LM is a necessary precondition for LI, it is not sufficient since LM can have primary or secondary causes. In addition, there is no matching between symptomatology and a positive test for LI [ 109 ]. Lactase non-persistence (LNP) is the primary cause of LM, due to reduction in expression of lactase levels during the first two decades of life, while lactase persistence (LP) derives from specific mutations.…”
Section: Lactase Deficiency and Lactose Intolerancementioning
confidence: 99%
“…Lactase non-persistence (LNP) is the primary cause of LM, due to reduction in expression of lactase levels during the first two decades of life, while lactase persistence (LP) derives from specific mutations. Moreover, recent research showed that LNP may be an ancestral condition that following Mendelian genetics and its prevalence is based not only on individual genetics but also on region of origin, with higher frequency in individuals of Asian, African, and South American, and lower in those of northwestern and Indian northern European origin [ 85 , 109 ]. Different causes lead to LD, which distinguish each of the distinct four types: Primary Lactase Deficiency : defined also as adult-type LD, is a common autosomal recessive inherited condition characterized by a progressive reduction in lactase activity; in fact, it results from a regulated change in the lactase gene expression during the life span [ 90 , 110 , 111 ].…”
Section: Lactase Deficiency and Lactose Intolerancementioning
confidence: 99%
“…Lactase non-persistence (LNP) is the primary cause of LM, due to reduction in expression of lactase levels during the first two decades of life, while lactase persistence (LP) derives from specific mutations. Moreover, recent research showed that LNP may be an ancestral condition that following Mendelian genetics and its prevalence is based not only on individual genetics but also on region of origin, with higher frequency in individuals of Asian, African, and South American, and lower in those of northwestern and Indian northern European origin [85,109]. Different causes lead to LD, which distinguish each of the distinct four types: Primary Lactase Deficiency: defined also as adult-type LD, is a common autosomal recessive inherited condition characterized by a progressive reduction in lactase activity; in fact, it results from a regulated change in the lactase gene expression during the life span [90,110,111].…”
Section: Lactase Deficiency and Lactose Intolerancementioning
confidence: 99%
“…It is noteworthy to add that the success of alternative approaches is also linked to the fact that patients may prefer not to take medications, especially for extended periods. More than 80% of individuals with IBS symptoms note connections to food and frequently modify their diets as a means to enhance their condition, opting for dietary adjustments (e.g., gluten-free diets (GFDs) and elimination diets based on IgG antibody testing) instead of resorting to medications, although their efficacy lacks robust supporting data [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%